A Room with a View - Forster, E. M. (Edward Morgan), 1879-1970 (Salt Lake City, UT : Project Gutenberg, 2001)
"A Room with a View" by E. M. Forster is a novel published in 1908. Young Lucy Honeychurch travels to Italy with her uptight cousin as chaperone, where an unexpected encounter with the unconventional George Emerson stirs confusing emotions. Back in England, Lucy becomes engaged to the sophisticated but pompous Cecil Vyse. When the Emersons move nearby, Lucy must confront her true feelings and decide between societal expectations and genuine passion in Edwardian England's restrained culture. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Room_with_a_View
Release date is 2001-05-01
Keywords: Humorous stories; England -- Fiction; Young women -- Fiction; British -- Italy -- Fiction; Florence (Italy) -- Fiction